The role of community media for social wellbeing - Thangaraja, C.S. (University of Colombo, Sri Lanka., 2019)
Active participation and contribution of marginalised societies can be helpful in achieving social wellbeing as meaningful realisation. The factors which are important to social wellbeing can be identified in five sections. Among these, the most important factor is ‘social acceptance'. It is the most effective and significant part of social wellbeing. In the concept of social wellbeing, marginalised groups can be rehabilitated to be active members of the society through the application of different strategies. Communication can be performed as the most relevant strategy in this process. The concept of communication can be defined in light of several tasks such as creating mutual and meaningful relationships with others and providing support to uphold those social relationships. The objectives of the study are to identify the role and tasks of communication in assisting marginalised people to overcome their loneliness and decrease the burden and negative impacts of their unfortunate experiences, to recognise the supportive role of the community media for those traumatised people to get rid of their pathetic past, and to describe the importance of communication to enrich their lifestyles. In the end, these circumstances would reinforce the notion of social wellbeing by physical, mental, and social standards. Case studies and in-depth interviews are used as the main research methods in this study. Rohingya refugee camps in Nepal and Bangladesh were selected as the sample of the study and six in-depth interviews were conducted at each camp with refugees and community media journalists. Data has been subjected to content analysis. The study recognized that traumatised marginalised groups can be empowered by communication. Community media can play an energetic role in this communication process by positively affecting a person's attitude and behavior to ensure the wellbeing of marginalised societies. Considering the findings, it can be suggested that communication strategies of community media would promote the wellbeing of society.
Keywords: community media, marginalised society, social wellbeing, traumatised people